2023
DOI: 10.1002/bdr2.2207
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis during pregnancy: A way to transfer an impairment to later life

Sina Motamedi,
Reza Saboori Amleshi,
Behnoush Akbari Javar
et al.

Abstract: Epidemiological studies examining the influence of cannabis across the lifespan show that exposure to cannabis during gestation or during the perinatal period is associated with later‐life mental health issues that manifest during childhood, adolescence, and adulthood. The risk of later‐life negative outcomes following early exposure is particularly high in persons who have specific genetic variants, implying that cannabis usage interacts with genetics to heighten mental health risks. Prenatal and perinatal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 136 publications
(219 reference statements)
1
2
0
Order By: Relevance
“…Prenatal exposure to alcohol, nicotine, or cannabis in rodents has been shown to produce a wide range of behavioral changes in the offspring that may begin early in life and last long into adulthood, with parallel effects observed in human studies. There are several comprehensive reviews of the behavioral outcomes of prenatal exposure to these drugs of abuse [45][46][47][48], with some reports examining rodents at a young age [49][50][51][52][53][54]. In a recent study from our laboratory [4], we demonstrated in early postnatal rats that prenatal exposure to alcohol, at a relatively low concentration and for only 5 days, produces a number of drug-induced behaviors in the offspring, consistent with those described in clinical studies of children [26,[55][56][57][58][59].…”
Section: Behavioral Disturbances Observed In Rodent Studiessupporting
confidence: 77%
See 2 more Smart Citations
“…Prenatal exposure to alcohol, nicotine, or cannabis in rodents has been shown to produce a wide range of behavioral changes in the offspring that may begin early in life and last long into adulthood, with parallel effects observed in human studies. There are several comprehensive reviews of the behavioral outcomes of prenatal exposure to these drugs of abuse [45][46][47][48], with some reports examining rodents at a young age [49][50][51][52][53][54]. In a recent study from our laboratory [4], we demonstrated in early postnatal rats that prenatal exposure to alcohol, at a relatively low concentration and for only 5 days, produces a number of drug-induced behaviors in the offspring, consistent with those described in clinical studies of children [26,[55][56][57][58][59].…”
Section: Behavioral Disturbances Observed In Rodent Studiessupporting
confidence: 77%
“…Behavioral changes have also been observed in young rodents, as shown by altered locomotor activity in pre-weanling rats [68] and increased anxietylike and impulsive behaviors in adolescent rats [69]. Prenatal exposure to cannabis in rodents has similar effects on drug-related behaviors [48,70,71], including a small increase in anxiety and impulsive risk-taking behavior during adolescence [72,73]. Further, longlasting alterations in drug-seeking behavior have been shown after prenatal exposure to tetrahydrocannabinol (THC), the primary psychoactive molecule in cannabis that crosses the fetoplacental barrier [74], which include an increase in behavioral sensitivity to this drug in pre-adolescent rats [73] and also in heroin self-administration in adult rats [75].…”
Section: Behavioral Disturbances Observed In Rodent Studiesmentioning
confidence: 98%
See 1 more Smart Citation